Structural Equation Modeling (SEM) untuk Mengukur Pengaruh Pelayanan, Harga, dan Keselamatan terhadap Tingkat Kepuasan Pengguna Jasa Angkutan Umum Selama Pandemi Covid-19 di Kota Ambon - Zakheus Putlely; Yopi Andry Lesnussa; Abraham Z Wattimena; Muhammad Yahya Matdoan (Indonesian Journal of Applied Statistics, 2021)
Structural Equation Modeling (SEM) is a statistical analysis technique used to build and test statistical models in the form of causal models. Large-Scale Social Restrictions (PSBB) are government policies to break the chain of spreading the corona virus (Covid-19). This policy certainly has an impact on drivers of public transport services. This research shows that the passengers are very satisfied with the travel safety factor. Meanwhile, service factors and passenger public transport fares are in the satisfied category. Furthermore, the variable service quality (MP), the price of public transportation (H), and passenger safety (KP) have an influence on passenger satisfaction. Because the t-value is greater than 1.96 (for the real level of 5%). The influence of service quality, price and safety variables on passenger satisfaction is 78.1%, the remaining 21.9% is influenced by other variables outside the research.Keywords: covid-19, structural equation modeling, satisfaction.